Towards a Compact Thin-Disk-Based Femtosecond XUV Source - Pronin, Oleg (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2014)
This thesis provides unique information on the Kerr-lens mode-locking (KLM) technique applied to a thin-disk laser. It describes in detail cavity geometry, the qualitative approach to KLM, and self-starting behavior in the regime of both negative and positive dispersion. Comprehensive comparative analysis of KLM and semiconductor saturable absorber techniques is also carried out. Recent successful experiments on carrier-envelope phase stabilization, spectral broadening and compression of output of this oscillator underline the importance of this new, emerging technology.